2020
DOI: 10.1002/adsc.202000020
|View full text |Cite
|
Sign up to set email alerts
|

DBSA‐Catalyzed Regioselective Dehydrative Friedel‐Crafts Arylation of CF3‐Containing 3‐Indolyl(2‐thiophenyl)methanols with 2‐Substituted Indoles in Water

Abstract: A green and efficient regioselective dehydrative Friedel‐Crafts arylation of trifluorinated 3‐indolyl(2‐thiophenyl) methanols with 2‐substituted indoles, catalyzed by DBSA (dodecylbenzenesulfonic acid) in water is described. This simple and atom‐economical protocol features a unique regioselective 1,8‐addition, operational simplicity, mild conditions, excellent functional group compatibility, and environmental benignity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…[69] Rao and co-workers later demonstrated that 3indolyl(2-thiophenyl)methanols bearing a CF 3 group can also undergo dehydration under acidic conditions, followed by the addition of nucleophiles such as indoles and phenols. [73] The main results of this crosscoupling reaction with phenols are illustrated in Scheme 26. The reaction proceeded at the C5 position of the thiophene moiety in the presence of a catalytic amount of dodecylbenzenesulfonic acid in water.…”
Section: Other Methods Of Cross-couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…[69] Rao and co-workers later demonstrated that 3indolyl(2-thiophenyl)methanols bearing a CF 3 group can also undergo dehydration under acidic conditions, followed by the addition of nucleophiles such as indoles and phenols. [73] The main results of this crosscoupling reaction with phenols are illustrated in Scheme 26. The reaction proceeded at the C5 position of the thiophene moiety in the presence of a catalytic amount of dodecylbenzenesulfonic acid in water.…”
Section: Other Methods Of Cross-couplingmentioning
confidence: 99%
“…Rao and co‐workers later demonstrated that 3‐indolyl(2‐thiophenyl)methanols bearing a CF 3 group can also undergo dehydration under acidic conditions, followed by the addition of nucleophiles such as indoles and phenols [73] . The main results of this cross‐coupling reaction with phenols are illustrated in Scheme 26.…”
Section: Cdc Reaction Of Phenols With π‐Excessive Heterocyclesmentioning
confidence: 99%
“…However, to the best of our knowledge, the synthetic potential of difluoromethylated 3‐indolylmethanols remains untapped. With our continuing interest in exploring the dehydrative cross‐coupling reactions of fluorinated 3‐indolylmethanols, [19a,e] we herein describe a green and practical catalyst‐free approach for the synthesis of 2‐phosphoryl‐3‐monofluorovinylindoles via a cascade regioselective dehydrative phosphorylation/stereoselective defluorination process starting from easily accessible difluoromethylated 3‐indolylmethanols and H ‐phosphine oxides (Scheme 1e). Notably, this protocol features catalyst‐ and additive‐free conditions, excellent regio‐ and stereospecificity, broad substrate scope, and environmental benignity.…”
Section: Methodsmentioning
confidence: 99%
“…The method was extended to the use of 6‐indolylmethanols as substrates, providing the products with impressive enantioselectivity for a remote 1,8‐addition. Rao and co‐workers subsequently found that 2‐substituted indoles undergo regioselective 1,8‐addition into vinyliminium intermediates derived from dodecylbenzenesulfonic acid (DBSA) catalysed dehydration of trifluoromethyl 3‐indolyl(2‐thiophenyl)methanols [51] . A wide range of thiophene‐centred bisindole products can be produced in good yields from a range of both reaction partners.…”
Section: Dehydrative C−c Bond Formationmentioning
confidence: 99%